Syntheses, analytical and pharmacological characterizations of the 'legal high' 4‐[1‐(3‐methoxyphenyl)cyclohexyl]morpholine (3‐MeO‐PCMo) and analogues. Issue 2 (26th July 2017) - Colestock, Tristan; Wallach, Jason; Mansi, Matt; Filemban, Nadine; Morris, Hamilton; Elliott, Simon P.; Westphal, Folker; Brandt, Simon D.; Adejare, Adeboye
Abstract : New psychoactive substances (NPS) are commonly referred to as 'research chemicals', 'designer drugs' or 'legal highs'. One NPS class is represented by dissociative anesthetics, which include analogues of the arylcyclohexylamine phencyclidine (PCP), ketamine and diphenidine. A recent addition to the NPS market was 4‐[1‐(3‐methoxyphenyl)cyclohexyl]morpholine (3‐MeO‐PCMo), a morpholine analogue of 3‐MeO‐PCP. Although suspected to have dissociative effects in users, information about its pharmacological profile is not available. From clinical and forensic perspectives, detailed analytical data are needed for identification, especially when facing the presence of positional isomers, as these are frequently unavailable commercially. This study presents the analytical and pharmacological characterization of 3‐MeO‐PCMo along with five additional analogues, namely the 2‐ and 4‐MeO‐PCMo isomers, 3, 4‐methylenedioxy‐PCMo (3, 4‐MD‐PCMo), 3‐Me‐PCMo and PCMo. All six arylcyclohexylmorpholines were synthesized and characterized using chromatographic, mass spectrometric and spectroscopic techniques. The three positional isomers could be differentiated and the identity of 3‐MeO‐PCMo obtained from an internet vendor was verified. All six compounds were also evaluated for affinity at 46 central nervous system receptors including the N ‐methyl‐d ‐aspartate receptor (NMDAR), an important target for dissociative anesthetics such as PCP and ketamine. In vitro binding studies using (+)‐[3‐ 3 H]‐MK‐801 in rat forebrain preparations revealed moderate affinity for NMDAR in the rank order of 3‐Me >3‐MeO > PCMo >3, 4‐MD > 2‐MeO > 4‐MeO‐PCMo. 3‐MeO‐PCMo was found to have moderate affinity for NMDAR comparable to that of ketamine, and had an approximate 12‐fold lower affinity than PCP. These results support the anecdotal reports of dissociative effects from 3‐MeO‐PCMo in humans. Abstract : Syntheses, analytical and pharmacological characterizations of the 'legal high' 4‐[1‐(3‐methoxyphenyl)cyclohexyl]morpholine (3‐MeO‐PCMo) and analogues are presented. 3‐MeO‐PCMo was differentiated from its 2‐MeO‐ and 4‐MeO‐PCMo positional isomers using multiple analytical techniques. All six arylcyclohexylmorpholines were found to be moderate‐affinity NMDA receptor antagonists, with some compounds having additional affinities for monoamine transporters including the dopamine and serotonin transporters.